The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00198-010-1249-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in relation to obesity, bone mineral density, bone turnover markers and vitamin D receptor genotypes in healthy Saudi pre- and postmenopausal women

Abstract: Vitamin D deficiency is highly prevalent among healthy Saudi pre-and postmenopausal women and largely attributed to obesity, poor exposure to sunlight, poor dietary vitamin D supplementation, and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
117
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 74 publications
(100 reference statements)
21
117
6
Order By: Relevance
“…20 Similarly, the same authors in another study reported a prevalence of vitamin D deficiency among Saudi women of 80%, 21 which is lower compared with our figure (98%). Our higher prevalence might be attributed to the fact that our sample is clinic-based, compared with their community-based sample.…”
Section: Discussioncontrasting
confidence: 48%
“…20 Similarly, the same authors in another study reported a prevalence of vitamin D deficiency among Saudi women of 80%, 21 which is lower compared with our figure (98%). Our higher prevalence might be attributed to the fact that our sample is clinic-based, compared with their community-based sample.…”
Section: Discussioncontrasting
confidence: 48%
“…A moderate positive correlation of25(OH)D with BMD measured by DEXA was found as 50% of subjects with hypovitaminosis D had low BMD. 31.8% of them were osteopenicand 18.1%had osteoprosis.These findings cope with the results of Bacon etal (40) ,Arabietal (41) ,Ardawietal (42) .Multiple regression analysis revealed that sun exposure was the main determiningfactore for 25(OH)D status.…”
Section: Discussionsupporting
confidence: 81%
“…Another study reported that VD deficiency was highly prevalent among studied Saudi women who suffer from obesity, poor sunlight exposure and poor dietary VD supplementation [27]. In our study, the significant low level of VD compared to normal BMI controls can be explained by several mechanisms.…”
Section: Discussionsupporting
confidence: 46%